Intrauterine Misoprostol Versus Intravenous Oxytocin for the Prevention of Primary Postpartum Hemorrhage During Cesarean Section: A One-Year Randomized Controlled Trial (Eastern Medical College Journal, 2026)
Background: Postpartum haemorrhage (PPH) is the major cause of maternal death worldwide, significantly in poor countries, like Asia, Africa. In our country PPH is the major cause of maternal mortality (about 80%). Global studies for decades showed that maternal mortality following PPH is due to uterine atony following vaginal delivery, caesarean section delivery and use of uterotonic drugs are the choice for both prevention and treatment of PPH. This study aims to evaluate the use and efficacy of intrauterine misoprostol versus oxytocin alone, in controlling postpartum haemorrhage due to atonic uterus amongst women with undergone Caesarean section in a tertiary care hospital setting of Bangladesh.Material and Methods: This randomized clinical trial was done in the Department of Obstetrics & Gynecology, Eastern Medical college Hospital, Cumilla, Bangladesh between January 2022 to December 2022. A total of 100 participants were randomly selected from all patients who admitted for elective cesarean section within this period. In this, the study group (Group A=50), received only intrauterine misoprostol after placental delivery. On the other hand, in control group (Group B=50) received routine intravenous Oxytocin alone.Results: There were no significant differences in baseline characteristics between the two groups. Group A (misoprostol) showed significantly lower preoperative, post-operative, and total blood loss compared to Group B (oxytocin). Post-operative hemoglobin and hematocrit levels were significantly higher in Group A (p